Guidance and Counselling Services through Online Content Development: an Innovative Approach in the Digital Era - Irene Maya Simon; Henny Indreswari; Devy Probowati; Riskiyana Prihatiningsih; Awalya Siska Pratiwi (Bisma The Journal of Counseling, 2025)
In this age, digital technology has become integral to various aspects of life, including education and counselling services. In this context, guidance and counselling services require innovation in both methods and media to address the challenges and needs of the digital generation. This study aims to develop content for the BKONLINE platform as an innovative approach in the digital era. The research employs a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), which aims to produce a product that meets quality standards and user needs. The research stages include needs analysis, platform design, content development, implementation, and evaluation by experts and prospective users. The study participants consist of guidance and counselling experts, educational technology media specialists, and students as potential users of the product. Validation results indicate that the developed product meets acceptance criteria from both expert and user perspectives. The BKONLINE platform is expected to enhance the accessibility, effectiveness, and personalization of guidance and counselling services, supporting students’ personal, academic, social, and career development.